Pengaruh Customer Experience dan Service Quality Terhadap Customer Loyalty Dengan Customer Satisfaction Sebagai Variabel Intervening: (Studi Kasus pada Semula Coffee) - Putri Wulandari; Hawik Ervina Indiworo; Ratih Hesty Utami Puspitasari (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of customer experience and service quality on customer loyalty, with customer satisfaction as an intervening variable among Semula Coffee customers. This study employs a quantitative approach using a survey method by distributing questionnaires to Semula Coffee customers. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of the SmartPLS application. The results show that customer experience has a positive effect on customer loyalty and customer satisfaction. Service quality does not have a direct effect on customer loyalty, but it has a positive effect on customer satisfaction. Furthermore, customer satisfaction has a positive effect on customer loyalty and mediates the relationship between customer experience, service quality, and customer loyalty. These findings indicate that customer experience and service quality play an important role in increasing customer satisfaction, which ultimately strengthens customer loyalty.